Malawi: an atlas of social statistics - Benson, Todd (Government Statistical Office, Government of Malawi, 2002)
This atlas combines information and analyses of the 1998 Population and Housing Census and the 1997-98 Integrated Household Survey, together with some sectorally specific data, to provide policy makers, students, educators and interested individuals with a better and more up-to-date understanding of the spatial distribution of the characteristics and living conditions of the people of Malawi. Although a broad range of social statistics are considered in the atlas, the over-riding focus is on poverty. The spatial patterns seen in the atlas will provide the reader with insights regarding key geographic facors associated with poverty, thereby assisting in the development and in the geographic targeting of programs designed to reduce it." from Back Cover.